How To Manage Social Media Hoaxes - Indiwan Seto Wahjuwibowo; Yoyoh Hereyah (Jurnal InterAct, 2016)
Social  media  in  Indonesia  is  very  popular  and  many  people  are  addicted  to  it. Information, both bad and good occur in social media, moreover the health sector. Facebook, Path and Twitter are filled with various information about lifestyle, technique to maintain health, nutrition and tips face malignancy and how to prevent it. In the offline world, communities are typically responsible for enforcing norms of privacy and general etiquette. In the online world, new etiquette challenges abound. To reap the benefits of socializing and making new friends, teens often disclose information about themselves that would typically be part of an acceptable “getting-to-know-you” process offline (name, school, personal interests, etc.). On social network sites, these stories are posted online sometimes in full public view. In some cases, this information is innocuous or fake. But in other cases, disclosure reaches a level that is troubling for parents and those concerned about the safety of online teens, and once children put this information online, they will never get it back. On Facebook and other social media app due its anonym, and immediately, everyone can easily convey information including in the field of health, and not just whether he was expert or not. Social media can be shared quickly, therefore information distribution to various parties seamless. The problem, not necessarily all information about health is valid and literally capable, danger when wrong health information was followed without have being reviewed.